2019
DOI: 10.5603/kp.a2018.0243
|View full text |Cite
|
Sign up to set email alerts
|

The obesity paradox in patients undergoing transcatheter aortic valve implantation: is there any effect of body mass index on survival?

Abstract: A b s t r a c tBackground: Conflicting results have been presented regarding the influence of body mass index (BMI) on outcomes among patients undergoing transcatheter aortic valve implantation (TAVI). Aims:To investigate the impact of BMI on clinical outcomes after TAVI.Methods: A total of 148 consecutive patients were categorised using baseline BMI according to the World Health Organization criteria. Baseline patient characteristics, frailty, and procedural and clinical outcomes including 30-day and 12-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Calculation of BMI has been widely used in risk stratification with conflicting results. We have also found that BMI was not associated with mortality (17,52). The serum albumin is a good indicator of malnutrition.…”
Section: Discussionmentioning
confidence: 53%
“…Calculation of BMI has been widely used in risk stratification with conflicting results. We have also found that BMI was not associated with mortality (17,52). The serum albumin is a good indicator of malnutrition.…”
Section: Discussionmentioning
confidence: 53%
“…1,11,15,16,21,25,27,29,32,40,41,[43][44][45][46][47][48][49][51][52][53][54][55] Similar to previous studies, it was patients with low BMI that tended to have inferior outcomes. 1,21,29,41,44,45,47,50,51,[53][54][55] Second, postoperative complications such as MI, stroke, reoperation rates, AKI, new renal failure, requirement of dialysis, were postoperative bleeding are either superior in patients with higher BMI or equivalent to their normal BMI counterparts. 1,11,15,16,21,25,27,29,32,[40][41][42][43][44]…”
Section: Postoperative Complicationsmentioning
confidence: 86%
“…Patients with underweight were found to have high risk of AKI with 54 Vaduganathan et al found rates of postoperative MI and stroke did not differ between groups, but rates of reoperation were significantly different between groups. 2%, 2%, 1% and 3% (p = .04) of patients with underweight, normal weight, overweight and obesity required reoperation.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Tokarek et al showed that increased BMI was independently associated with 1-year survival benefit after TAVR. However, there was no difference between the groups in terms of 30-day allcause mortality [5].…”
Section: Introductionmentioning
confidence: 73%